2015
DOI: 10.1039/c4ew00030g
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and understanding of amido black 10B dye degradation in aqueous solution by electrocoagulation with the conventional oxidants peroxomonosulfate, peroxodisulfate and hydrogen peroxide

Abstract: Degradation of amido black 10B dye by electrocoagulation processes assisted by conventional oxidants: peroxomonosulfate, peroxodisulfate and hydrogen peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Based on the results it may be concluded that the oxidative degradation of dye in presence of AgNPs by K 2 S 2 O 8 is radical ion based mechanism and the main radical ion species generated during the catalytic activation of K 2 S 2 O 8 was sulphate radical ions (SO 4 •− ). The role of the catalyst as a mediator for the electron transfer to PDS was also reported [ 32 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results it may be concluded that the oxidative degradation of dye in presence of AgNPs by K 2 S 2 O 8 is radical ion based mechanism and the main radical ion species generated during the catalytic activation of K 2 S 2 O 8 was sulphate radical ions (SO 4 •− ). The role of the catalyst as a mediator for the electron transfer to PDS was also reported [ 32 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…These methods have significant disadvantages such as incomplete color removal, production of harmful side products, efficacy only in low concentration, expense and high energy requirement. Of late, practically sound advanced oxidation processes (AOPs) came into existence which include Fenton 18 19 , photo-Fenton 20 , ozonization 21 , TiO 2 photocatalysis 22 23 , photolysis using H 2 O 2 24 25 and O 3 26 etc. One of the highly promising and cost effective AOPs is the use of TiO 2 (anatase), a semiconductor catalyst under UV radiation for the mineralization of organic pollutants 27 .…”
mentioning
confidence: 99%
“…61,62 Moreover, pH of solution is a main factor which inuences dye degradation as pH affects the surface charge properties of the catalyst. 63 Hence, to optimize reaction pH for AB-10B dye degradation, the considered range of pH was 3.0 to 9.0 as illustrated in Fig. 7A.…”
Section: Degradation Stability and Recyclability Of Cu/h 3 Btc Mofmentioning
confidence: 99%